Assessment of the Allocation of HIV Funding in Indonesia - Gray, Richard T. (World Bank, Washington, DC, 2018)
This study aimed to estimate the cost-effectiveness and return on investment of HIV programs implemented during 2003-2010 in Indonesia and to contribute to the allocative efficiency of the HIV prevention response in Indonesia through analyses to inform the prioritization of resources for the 2015-2019 national HIV budget in the context of reductions in international donor funding. The spending-outcome relationships and epidemiological model were used to compare observed conditions with counterfactual scenarios of reduced/no programs to calculate he cost-effectiveness and estimate healthcare costs saved and thus the return on investment. Model simulations of epidemic projections over many combinations of possible resource allocations were used to identify optimal allocations for reducing new infections over the next HIV budget period.